Efeito de beauveria bassiana (bals.) Vuillemin e Metarhizium anisopliae (metsch.) sorokin nos parâmetros biológicos de trichogramma atopovirilia oatman & platner, 1983 (hymenoptera: trichogrammatidae) - Polanczyk, Ricardo Antonio [UNESP] (2010)
Two bioassays were performed to evaluate the effect of two biopesticides based on Beauveria bassiana (Bals.) Vuillemin and Metarhizium anisopliae (Metsch.) Sorokin on the biological parameters of Trichogramma atopovirilia Oatman & Platner, 1983. In the first one, displays with S. frugiperda, 1797 eggs were dropped into the biopesticide suspension and offered to the parasitoid females for 24 hours. In the second one, parasitoid females were fed with a suspension containing honey and biopesticide suspension. In both cases, after the parasitoid death they were mantained into a humid chamber to observe fungus sporulation. The experiments were maintained in a climatized chamber at 25±1º C, RH 70± 10%, and photophase of 14 hours. The longevity and adult mortality, total parasitism, progeny emergency, number of individuals per egg and sexual ratio were analyzed. The biopesticides did not affect the evaluated parameters and no fungus sporulation was observed in dead females. It is possible to assert that the entomopathogenic fungi B. bassiana and M. anisopliae can be used with T. atopovirilia in IPM S. frugiperda systems.